Actin cores of hair-cell stereocilia support myosin motility. - Shepherd, G M (1990)
The actin cores of hair-cell stereocilia were tested as a substrate for the movement of myosin-coated beads in an in vitro assay. Large numbers of stereocilia from bullfrog sacculi and semicircular canals were isolated by blotting onto coverglasses and were demembranated to expose the polar actin tracks of their cytoskeletal cores. Silica or polystyrene beads, coated with thick filaments of chicken skeletal muscle myosin, were added to this core preparation in the presence of ATP. Myosin-coated beads could reach some of the cores by diffusion alone, but the efficiency and precision of the assay were improved considerably by the use of "optical tweezers" (a gradient-force optical trap) to deposit the beads directly on the cores. Beads applied in this fashion bound and moved unidirectionally at 1-2 microns/s, escaping the retarding force of the trap. Actin filaments within the stereocilia are cross-linked by fimbrin, but this did not appear to interfere with the motility of myosin. Beads coated with optic-lobe kinesin were also tested for movement; these bound and moved unidirectionally at 0.1-0.2 microns/s when applied to microtubule-based kinociliary cores, but not when applied to actin-based stereociliary cores. Our results are consistent with, and lend support to, a model for hair cell adaptation in which a molecular motor such as myosin maintains tension on the mechanically gated transduction channels. Optical tweezers and video-enhanced differential interference contrast optics provide high efficiency and improved optical resolution for the in vitro analysis of myosin motility.